A participatory framework proposal for guiding researchers through an educational mobile app development - Tavares, Rita (2021)
The research work reported in this article is part of a wider study aimed at developing a mobile application (app) for Science Education in primary school. For that, we designed a participatory framework proposal nested within the larger framework of Educational Design Research. This framework emerged from the authors’ need to organise the different phases of the mobile apps development and to arrange the expected products that arise from them. Our framework suggests a grounded, participatory and user-centred approach, relating literature contributions with data collected among future end-users. In this study, we exemplify the implementation of the proposed framework by presenting the outcomes of a specific moment of the preliminary research: students’ stories and drawing analysis, to define the mobile app concept. For that, we (1) present and describe the participatory framework proposal, (2) identify and characterise the research method adopted to define the mobile app concept, (3) reveal and analyse data collected from the implementation of a creative writing and drawing activity performed by fourth grade primary-school students, and (4) describe the implications of data analysis in the mobile app concept definition. Our intention is to share with other educational researchers an approach that can be used to develop educational mobile apps grounded on future end-users’ perceptions and ideas. We also aim to contribute to deepen the Educational Design Research apps by proposing and exemplifying the implementation of a framework that brings together researchers, students, teachers and experts.